Intestinal Flora as a Potential Strategy to Fight SARS-CoV-2 Infection - He, Li-Hong; Ren, Long-Fei; Li, Jun-Feng; Wu, Yong-Na; Li, Xun; Zhang, Lei (Frontiers in microbiology, 2020)
The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread rapidly worldwide, seriously endangering human health. In addition to the typical symptoms of pulmonary infection, patients with COVID-19 have been reported to have gastrointestinal symptoms and/or intestinal flora dysbiosis. It is known that a healthy intestinal flora is closely related to the maintenance of pulmonary and systemic health by regulating the host immune homeostasis. Role of the "gut-lung axis" has also been well-articulated. This review provides a novel suggestion that intestinal flora may be one of the mediators of the gastrointestinal responses and abnormal immune responses in hosts caused by SARS-CoV-2; improving the composition of intestinal flora and the proportion of its metabolites through probiotics, and personalized diet could be a potential strategy to prevent and treat COVID-19. More clinical and evidence-based medical trials may be initiated to determine the strategy.The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread rapidly worldwide, seriously endangering human health. In addition to the typical symptoms of pulmonary infection, patients with COVID-19 have been reported to have gastrointestinal symptoms and/or intestinal flora dysbiosis. It is known that a healthy intestinal flora is closely related to the maintenance of pulmonary and systemic health by regulating the host immune homeostasis. Role of the "gut-lung axis" has also been well-articulated. This review provides a novel suggestion that intestinal flora may be one of the mediators of the gastrointestinal responses and abnormal immune responses in hosts caused by SARS-CoV-2; improving the composition of intestinal flora and the proportion of its metabolites through probiotics, and personalized diet could be a potential strategy to prevent and treat COVID-19. More clinical and evidence-based medical trials may be initiated to determine the strategy.